Namizni tenis - Kondrič, Miran (Šport (Ljubljana), 2017)
Table tennis is an extremely demanding and complex sport. Learning and mastering the correct techniques requires a lot of effort, denial and will from a child. As part of this, children's effective performance in the game can only be ensured by appropriate equipment and the reliable accomplishment of basic exercises. One should consider several things when purchasing a table tennis racket. The choice of racket should be left to the table tennis coach and not to parents and shop assistants. Before buying a racket, it is good to know what a sports store offers and for whom we are making the purchase. The ideal would be a link between future coaches, parents and a sports shop selling table tennis rackets. The advice and buying of a racket with the trainer's assistance can lead to the child's extra motivation and above all confidence in the coach as confirmed by the child's parents in the selection and purchase of the racket.
Keywords: adapted equipment; children; drža loparja; grip; lopar; namizni tenis; otroci; prilagojeni rekviziti; racket; sport; šport; table tennis